Does Spending Time in Public Settings Contribute to the Adolescent Risk of Violent Victimization? - Felson, Richard B. (Journal of quantitative criminology, 2013)
Objectives Using data from a nationally representative survey of adolescents in Finland this research examined the influence of spending time in public settings on the risk of physical assault and robbery victimization. Methods Binary and multinomial regression models were estimated to disaggregate associations between hours spent in public settings and characteristics of the victimization incident. The amount of causality/spuriousness in the association was examined using a method of situational decomposition. Results Our findings indicate that: (1) an active night life (any time after 6 pm) has a strong effect on victimization for boys, whereas much of the association between night life and victimization is spurious for girls; (2) after-school activity is not a risk factor; (3) adolescents who frequent public places at night increase their risk of victimization by people they know as well as strangers; and (4) much of the risk of night time activity in public settings is alcohol-related. Conclusions Our research suggests that a good deal of the risk associated with spending time in public settings is a function of the victim’s own risky behavior rather than inadvertent physical contact with motivated offenders in the absence of capable guardians. In addition, this lifestyle is significantly more victimogenic for males.